Metabolomics in immunology research - Dalkiliç, Semih; Dalkiliç, Lütfiye Kadioğlu (Nova Science Publishers, Inc., 2023)
Metabolomics is the large-scale study of small molecules produced from the metabolic activities of the organism, and these molecules are generally called metabolites. The relationships of these metabolites with each other and with the biological system are called the metabolome. Unlike genomics, proteomics and transcriptomics, metabolomics is a field of study that examines in a broad spectrum of all metabolic activities in organisms. These metabolites are commonly divided into two groups, targeted and untargeted: targeted metabolites are based on quantitative methods that allow the metabolite concentration to be measured; and untargeted metabolites are those that envisage the simultaneous evaluation of large-scale metabolites without any prior sample information to form hypotheses. It is also suitable for describing changes in different pathophysiological conditions. There are many considerations about the functions of metabolic processes and individual metabolites, and important information has been recorded. They have important roles in immune cells. To identify metabolites that explain how the immune system works, the use of mass spectrometry and NMR spectroscopy-based platforms provides important biomarkers of how the immune system functions. This section gives important clues about how metabolomics is used in the immunology field. In particular, future roles of metabolomics in the immune system will be discussed. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: Biomarkers; Immune cells; Immune system; Mass spectrometry; Metabolomics